Prevalence of HIV infection among non-elderly individuals with hepatitis C in Japan: a population-based cohort study using a health insurance claim data - Ikeuchi, Kazuhiko; Okushin, Kazuya; Saito, Makoto; Adachi, Eisuke; Tsutsumi, Takeya; Takura, Tomoyuki; Yotsuyanagi, Hiroshi (BMC infectious diseases, 2022)
Hepatitis C virus (HCV) has been mainly transmitted through injection drug use, but recently, sexual transmission among men who have sex with men (MSM), which is also a major route of HIV transmission, is increasing. However, the prevalence of HIV and the incidence of other sexually transmitted infections (STIs) among HCV patients have been rarely reported. Using a healthcare insurance claim data of employees and their dependents covering seven-million people in Japan, we evaluated HIV prevalence among HCV patients aged 20-59 years. Hemophilia patients were excluded. HIV and HCV were defined by registered diagnoses and receiving viral RNA testing. The time course of HCV and HIV infections was analyzed. Incidences of syphilis, amebiasis, chlamydia, gonorrhea, hepatitis A, and hepatitis B were assessed. From April 2012 to August 2018, 6,422 HCV patients were identified. HIV prevalence was 0.48% (31/6422, 95% CI [confidence interval]: 0.33-0.68%). HIV was diagnosed after HCV in 3.2% (1/31), before HCV in 58.1% (18/31), and concurrently in 38.7% (12/31). Compared with HCV patients without HIV infection, HCV/HIV co-infected patients were younger (median age, 37 vs 51 years, p < 0.001), more likely to be male (30/31 [96.8%] vs 3059/6391 [47.9%], p < 0.001), more likely to have other STIs (38.7% [12/31] vs 0.9% [56/6391], p < 0.001), and live in Tokyo, the most populous capital city in Japan (67.7% [21/31] vs 11.6% [742/6391], p < 0.001). In Tokyo, the HIV prevalence among 20-30 s male with HCV was 18.6% (13/70; 95% CI, 10.3-29.7%). HIV prevalence among young male HCV patients was very high in Tokyo. HCV/HIV co-infected patients were more likely to acquire HIV before HCV, which is a known feature of MSM. They also had a higher incidence of STIs. These findings suggest that HCV might be prevalent as an STI among MSM particularly in Tokyo.